Status and Future of the EDEN ISS Mobile Test Facility - Vrakking, Vincent; Zabel, Paul; Zeidler, Conrad; Schubert, Daniel; Dorn, Markus (2020 International Conference on Environmental Systems, 2020)
Vincent Vrakking, German Aerospace Center (DLR), DE Paul Zabel, German Aerospace Center (DLR), DE Conrad Zeidler, German Aerospace Center (DLR), DE Daniel Schubert, German Aerospace Center (DLR), DE Markus Dorn, German Aerospace Center (DLR), DE ICES204: Bioregenerative Life Support The proceedings for the 2020 International Conference on Environmental Systems were published from July 31, 2020. The technical papers were not presented in person due to the inability to hold the event as scheduled in Lisbon, Portugal because of the COVID-19 global pandemic. Within the EDEN ISS project an international consortium designed and built a (semi-)closed loop greenhouse, called the Mobile Test Facility, to investigate and validate techniques for plant cultivation in future bioregenerative life support systems. At the end of 2017 the Mobile Test Facility, consisting of two modified 20 foot shipping containers, was transported to the German Neumayer Station III in the Antarctic for testing in a space-analogue environment. Following arrival in the Antarctic in January 2018, and initial system check-out activities, the Mobile Test Facility began its first operational phase in February 2018 which was concluded in November 2018. During the following Antarctic summer season in January 2019 a maintenance crew went to Antarctica to overhaul some components of the facility. The first months of the winter season 2019 (February-April) the facility was not in use. Nominal operation continued in May the same year and went on until end of October. The nine people of the overwintering crew of the Neumayer Station III grew crops and maintained the greenhouse in that time. From December 2019 to February 2020, the next maintenance crew arrived from Europe bringing with them new components and resupply of consumables and spare parts. Nominal operation started again in February 2020 with the new overwintering crew taking over the operation of the greenhouse. This paper describes results from the 2019 and early 2020 overwintering ...